Answer:
5 1/3 - 2 4/9 = 26/9
26/9 simplified equals 2 8/9
Step-by-step explanation:
I hope that my answer has helped you to understand you questions asked. If you have any further questions, please put them below.
Have a great rest of your day/night!
Answer: x = 54
Explanation:
180 - 14 = 166
3x + 4 = 166
3x = 162
x = 162/3 = 54
Answer and Step-by-step explanation:
![x^{2} - xy + x^{2} -xy\\\\2x^{2} -2xy](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-%20xy%20%2B%20x%5E%7B2%7D%20-xy%5C%5C%5C%5C2x%5E%7B2%7D%20-2xy)
This is the answer.
Step-by-step explanation: Arrange the terms in ascending order: -7, -2/5, 3/9, 11/12.
Hope this helps! :D
-TanqR